VD_FINDINFO Jug / 2013 / 311 vom 2. Oktober 2013 - VD Tribunal cantonal (2013)
JUGEMENT PAR DÉFAUT, MOTIVATION DE LA DÉCISION, OPPOSITIONPROCÉDURE, JUGE UNIQUE | 356 al. 4 CPP (CH), 398 al. 4 CPP (CH)